Formulation and Physical Characterization of Essential Oil Bangle (Zingiber cassumunar Roxb.) Nanoemulsion Gel - Purwanto, Ungsari Rizki Eka; Sholikhah, Mar’atus; Munisih, Siti (Journal of Science and Technology Research for Pharmacy, 2021)
Background: Bangle rhizome (Zingiber cassumunar Roxb) essential oil as long been used by Indonesian and often used by postpartum women, as a treatment for abdominal obesity. The formulation of bangle essential oil into topical preparations has not been widely reported. So far, bangle essential oil is not available in pharmaceutical dosage form. The users immediately apply essential oil to the abdominal area and previous study showed that the terpinene-4-ol only diffused 0,39% from 2 mg/cm2 of Bangle essential oil through skin membrane. The development of topical bangle essential oil is necessary to increase the effectiveness of the delivery of active substances through the skin and the comfort of the user. In order to increase the penetration of the terpinen-4-ol, the Bangle essential oil was formulated in the form of a nanoemulsion and then the nanoemulsion was dispersed into a gel base to increase user convenience. Aim: The aim of the present study was to investigate the potential of nanoemulsion formulations for Bangle essential oil and to know the optimum the composition of surfactants and cosurfactants in nanoemulsion system. This study also aims to determine the effect of base gel used in the nanoemulsion gel formulation on the appropriate physical properties. Method: The pre-emulsion was made beforehand with oil and a mixture of surfactant and cosurfactant. With the help of a Design Expert® ver. 10.0.1 software, component of sufactant and co-surfactant were optimized. The design formula was divided into seven nanoemulsion formulas with a ratio of Polysorbate 80: PEG 400, F1 (1: 8), F2 (8: 1), F3 (6,25: 2,75), F4 (8: 1), F5 (1: 8), F6 (1: 8), F7 (4,5: 4,5). The optimum consentration of Polysorbate 80 as surfactant and PEG 400 as co-surfactants in Bangle essential oil nanoemulsion was analyzed using simplex lattice design methode. The optimal formula was further evaluated for its distribution, droplet size, and zeta potential. Distilled water was used as the aqueous phase in nanoemulsion. The amount of aqueous phase: the amount of pre-emulsion is 9 : 1. The optimum nanoemulsion formula then dispersed in carbophol hydrogel to be nanoemulsion gel. Physical characterization of Bangle nanoemulsion gel like a pH, adhesion power, spreadability, viscosity before and after cycling test had been investigated. Result: The optimum composition of surfactant Tween 80 and co-surfactan PEG 400 was 7.659: 1.34. The results showed that the optimal formula with 2% Bangle Essential Oil Loaded in Nanoemulsion had the Z-average 95,2 nm with Index Polidispersity 0,176 and Zeta Potensial -0,1 mV. Bangle Nanoemulsion-Gel had a homogenous organoleptic, spreadability in 6,69 + 0.85 cm, adhesion power in 2.14 + 0.29 seconds, viscosity 5969 + 32.03 cps, and pH 6,58 + 0,29. Conclusion: Bangle Essential Oil Nanoemulsion-Gel formulation has the good physical characteristics and potentially be used as topical dosage forms. A further study is needed to determine the effectiveness of the treatment of abdominal obesity by topical administration of this preparation.